Jetstream—Early operations performance, adoption, and impacts. (2nd September 2018) - Hancock, David Y.; Stewart, Craig A.; Vaughn, Matthew; Fischer, Jeremy; Lowe, John Michael; Turner, George; Swetnam, Tyson L.; Chafin, Tyler K.; Afgan, Enis; Pierce, Marlon E.; Snapp‐Childs, Winona
Summary: Jetstream is a first of its kind system for the NSF — a distributed production cloud resource. We review the purpose for creating Jetstream, discuss Jetstream's key characteristics, describe our experiences from the first year of maintaining an OpenStack‐based cloud environment, and share some of the early scientific impacts achieved by Jetstream users. Jetstream offers a unique capability within the XSEDE‐supported US national cyberinfrastructure, delivering interactive virtual machines (VMs) via the Atmosphere interface. As a multi‐region deployment that operates as an integrated system, Jetstream is proving effective in supporting modes and disciplines of research traditionally underrepresented on larger XSEDE‐supported clusters and supercomputers. Already, Jetstream has been used to perform research and education in biology, biochemistry, atmospheric science, earth science, and computer science.